ORIGINS AND GENETIC DIVERSITY OF INTRODUCED POPULATIONS OF THE PUERTO RICAN RED-EYED COQUÍ, ELEUTHERODACTYLUS ANTILLENSIS, IN SAINT CROIX (U.S. VIRGIN ISLANDS) AND PANAMÁ - Barker, Brittany S. (Copeia, 2017)
The Red-eyed Coquí, Eleutherodactylus antillensis, is a terrestrial frog endemic to the Puerto Rican Bank (Puerto Rico and numerous islands and cays off its eastern coast), in the eastern Caribbean Sea. The species was likely introduced in Saint Croix, an island c. 100 km southeast of Puerto Rico, in the late 1930s, and in Panamá City, Panamá, in the late 1950s or early 1960s, but the source(s) of these introductions are unknown. We analyzed sequence data from one mtDNA locus and four nuDNA introns to infer the origin(s) of the Saint Croix and Panamá City populations and quantify their genetic diversity. Saint Croix and Panamanian populations do not share any haplotypes, and they cluster with different native populations, suggesting that they are derived from separate sources in the Puerto Rican Bank. Patterns of population structure trace the probable sources of E. antillensis in Saint Croix to islands off Puerto Rico’s eastern coast, which include Vieques, Culebra, Saint Thomas, Saint John, Tortola, and Virgin Gorda, and possibly to eastern Puerto Rico as well. In contrast, Panamá City E. antillensis probably originated from either western or eastern Puerto Rico. Genetic diversity in the introduced populations is similar to or lower than in populations in the species’ native range, indicating that genetic diversity has not increased in the alien frogs. Our findings may facilitate the development of preventive measures to minimize introductions of non-native amphibians in the Caribbean and Central America.